Students’ as Prospective Hospitality Specialists’ Competitiveness in Theory and Practice - Katane, Irēna; Īriste, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The goal of higher vocational education is to provide competitive hospitality specialists, who will be part of the emerging global labor market in the context of globalization. The objective of the article is to publish results of empirical and theoretical research. The results of the theoretical research show that in the substantiation of the specialists’ competitiveness are the same approaches inherent the personality’s competitiveness explanation and research, namely, the competitiveness is justified as set of qualities. Significant specialists’ competitiveness indicators from the professional point of view are marketability and employability. Main results of the experimental research demonstrate, students’ and scientists’ perceptions of issues relating to competitive personality are similar.